Diagnostika in zdravljenje zastrupitev z organskimi topili - Jamšek, Marija (Medicinski razgledi, 2009)
Organic solvents are a heterogeneous group of chemicals with different chemical structures which are usually used in the form of mixtures. They oftencontain toxic impurities or additives. Their toxicity depends on the solvent type and composition, as well as its route of administration and duration of exposure. During patient assessment, the physician has to considerthe toxicity characteristics of the solvent, along with its physical and chemical properties. The diagnosis of organic solvents poisoning should bebased on the patient's medical history, clinical examination and basic laboratory findings. After oral exposure, the patient's health may also be threatened by solvent aspiration. A proper differentiation between systemic toxicity and risk of solvent aspiration is crucial for choosing an appropriatemethod to decontaminate the gastrointestinal tract. In most cases of organic solvents poisoning, symptomatic treatment is sufficient. The article also presents triage recommendations for patients poisoned by an organic solvent.
Keywords: Carbohydrates; Ogljikovi hidrati; Poisoning; Topila; zastrupitve; Solvents; ogljikovodiki; diagnostika; organska topila; therapy; zdravljenje